Climate Change: Ecological and socio economic dimensions in the coastal zone - Azuz-Adeath, Isaac; Yañez Arancibia, Alejandro (My University, 2019)
This Editorial is the introductory text to the special section “Climate Change: Ecological and socio economic dimensions in the coastal zone” which is the result of the work developed to carry out the symposium of the same name held during the conference “EcoSummit 2016” in Montpellier, France, as well as the open call for papers published once the conference is over.
Ecological Engineering. The Journal of Ecosystem Restoration
Keywords: Climate change; Socio economic dimension; Coastal zone